SOCIALIZATION OF THE USE OF LIQUID ORGANIC FERTILIZER ON POTATO PLANTS IN JAGONG JEGET DISTRICT, ACEH TENGAH REGENCY: SOSIALISASI PENGGUNAAN PUPUK ORGANIK CAIR PADA TANAMAN KENTANG DI KECAMATAN JAGONG JEGET KABUPATEN ACEH TENGAH - Ruhalena Wilis; Ilya Puryani; Jauhari; Afdhalul Hilza (PT. ROCE WISDOM ACEH, 2026)
The purpose of this community service activity is to provide farmers with an understanding of the benefits and principles of using liquid organic fertilizer (LOF) to increase potato productivity and maintain soil fertility, improve farmers’ skills in making and applying LOF independently by utilizing local organic materials, and encourage the adoption of environmentally friendly technology in potato cultivation systems in the highlands of Aceh Tengah. Socialisation and Training were carried out in Jagong Jeget District, Central Aceh Regency, from July 8 to 10, 2025. The potato cultivation land belongs to a local farmer group (selected together with field agricultural extension workers). The results of the Community Service activity include increased farmer knowledge, improved practical skills in making LOF, greater adoption of technology, and greater environmental awareness. This socialisation activity successfully expanded potato farmers’ knowledge, skills, and understanding of LOF. The participatory and demonstrative methods used in the activity have proven effective in transferring appropriate technology to the farming community.